Identification of the Quality of Electronic Medical Records in Improving Health Services and Access to Technology to Increase Patient Satisfaction in Hospitals. - Langingi, Ake Royke Calvin; Pongantung, Henny (LPPM Institut Pendidikan Nusantara Global, 2025)
Electronic Medical Record (EMR) system brings major changes in the healthcare system. EMR transforms conventional medical records into digital medical records (EMR), thus addressing many issues, such as data loss (data security), difficulty reading handwriting, and the need for large storage space. By improving the quality of EMR, all its advantages will be reversed and will lead to patient satisfaction. The purpose of this study was to identify, understand, and analyze the quality of EMR in improving health services and technology access in improving patient satisfaction at Gunung Maria Hospital, Tomohon. This type of quantitative research with a cross-sectional study design , with a sample of 216 inpatients ( purposive sampling ), using a simple random sampling method with a probability sampling (PS) technique. Data were collected using a questionnaire. The results of the study obtained an R2 value of 0.993 (p = 0.000) on the predictor of service speed having a very strong and significant influence on patient satisfaction. On the predictor of data accuracy, the R2 value of 0.981 (p = 0.000), indicating that data accuracy is an important factor that has a very strong and significant influence on patient satisfaction. Information transparency predictor, R2 value = 0.983 (p = 0.000) which indicates that information transparency significantly influences patient satisfaction. In general, EMR quality (service speed, data accuracy and information transparency) influences patient satisfaction (p = 0.019). The results of the simultaneous test obtained that the predictor of service speed most influences patient satisfaction, with a value of p = 0.000. There is a need for a policy on service procedures in hospitals that includes service speed.